Crystallisation of organic molecules with a remarkably suppressed coffee-ring effect by a drop-drying process using binary solvent core–shell droplets. Issue 4 (11th July 2018) - Ahn, Yoolim; Park, Yohwan; Koo, Jin Young; Choi, Hee Cheul
Abstract : A modified drop-drying method was developed using a core–shell droplet which is spontaneously formed from a methanol/mesitylene binary solvent system. Abstract : A core–shell drop-drying (CSDD) method that employs spontaneous formation of a droplet-in-droplet system was newly presented for the efficient formation of molecular crystals. Well-defined methylene blue crystals were successfully obtained from the core–shell droplet with a significantly diminished coffee-ring effect.